NEW CHILEAN SPECIES OF XEROMELISSINAE (HYMENOPTERA: COLLETIDAE) (Acta Entomológica Chilena, 2022)
Two new species of Xeromelissinae are described, Chilimelissa rosie n.sp. from Toconao, II Región,Chile and Chilimelissa laureli n.sp from higher localities in the Andes Range, I Región, Chile.
Keywords: Chilimelissa, New species, Andes Range, Chile